Utilization Of Gravestone (Pilsbryoconcha Exilis) A Local Food Ingredients Source Of Protein: Pemanfaatan Kerang Kijing (Pilsbryoconcha Exilis) Sebagai Bahan Pangan Lokal Sumber Protein - Elvyrah Faisal; Bahja; Stevi Indriastuti Maharadi (Poltekkes Kemenkes Palu, 2022)
Food is one of the most important things in human survival and in terms of fulfilling a person's nutrients needed to grow and develop. In accordance with the diversity of resources, culture and local wisdom. Indonesia has a variety of local food sources that produce animal protein in the form of fish, shrimp, shellfish, and others. One source of animal protein that is still rarely known is freshwater clams or Gravestone (Pilsbryoconcha Exilis). People in the North Morowali or Morowali areas usually call the mussel (Pilsbryoconcha Exilis) as meti. One example of the use of this shellfish is making Chips. This Gravestone Chips (Pilsbryoconcha Exilis is made as an alternative to get protein intake. The purpose of this community service is to find out the development of Gravestone chips (Pilsbryoconcha Exilis). The results of community service showed that the results of the assessment before the counseling (pretest) were 27.3% of participants with good knowledge and there was an increase after attending the counseling (posttest) to 91.7%. The conclusion of this community service is that this activity has a good impact on participants in terms of knowledge about protein sources from local food and examples of their processing.